Childhood mediastinal masses in infants and children - Tansel, Türkan; Onursal, Ertan; Dayloğlu, Enver; Başaran, Murat; Sungur, Zerrin; Qamci, Emre; Yilmazbayhan, Dilek; Eker, Rukiye; Ertuğrul, Türkan (The Turkish Journal of Pediatrics, 2006)
We reviewed all cases of primary pediatric mediastinal masses diagnosed and treated over a 24-year period. In this study, out of 187 primary mediastinal mass cases diagnosed between 1980 and 2004 in Istanbul University Istanbul Faculty of Medicine, Cardiovascular Surgery Department, 37 pediatric primary mediastinal mass cases were retrospectively evaluated according to age, sex, symptoms, diagnostic procedure, anatomical location, surgical treatment, histopathological evaluation and postoperative adjuvant therapy. The patients ranged in age from 2 months to 15 years at the time of diagnosis, with a mean age of 8 years. There were 24 benign (64.8%) and 13 malignant (35.2%) tumors. The cases were lymphoma (27%), neurogenic tumors (21.6%), cystic lesions (18.9%), germ cell tumors (13.5%), thymic lesions (10.8%) and cardiac tumors (8.1%). Complete and partial resections of the tumor were the surgical procedures performed in 24 patients (64.8%) and 3 patients (8.1%), respectively. The three patients with a malignant tumor, in whom the entire mass could not be removed, received chemotherapy and radiation after surgery. In 10 patients with lymphoma, surgery was not a part of treatment and they received medical and radiation therapy after the establishment of the definitive diagnosis. All patients survived and were discharged from the hospital. Except for the cases with lyphoma, all patients are now free of recurrent disease. Compared to adults, children had more lymphomas and neurogenic tumors. Primary pediatric mediastinal malignancies are relatively common in infants and children. Lymphoma, neurogenic tumors and cystic lesions predominated. These differences between the age groups should also be considered when dealing with a mediastinal mass.